Moral Injury as a Transdiagnostic Risk Factor for Mental Health Problems in Detained Youth - Alexander, Ava R. (Criminal justice and behavior, 2024)
Youth who become involved in the juvenile justice system are at highly elevated risk for many emotional and behavioral problems. Past research has often focused on trauma exposure as a transdiagnostic risk factor in this population. However, distress resulting from perpetrating or witnessing acts that conflict with one’s deeply held moral beliefs, termed moral injury, may also play a role in predisposing these youth toward negative mental health outcomes. This study utilized a sample of 96 youth housed in secure detention centers and tested associations between exposure to potentially morally injurious events (PMIEs) and mental health outcomes, including anxiety, depression, posttraumatic stress, and nonsuicidal self-injury (NSSI). After controlling for trauma exposure and demographic variables, PMIEs were significantly and positively associated with symptoms of depression and anxiety, as well as engagement in NSSI. Implications for research and clinical practice are discussed.